PENGARUH GAYA KEPEMIMPINAN BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. ARIFINDO ADIPUTRA ARIAGUNA - Ardhan, Riyan Kusuma; Khan, Muhammad Asif; Bukhari, Eri (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to analyze the influence of leadership style, organizational culture, and work motivation on employee performance, with job satisfaction as a mediating variable. The research focuses on the employees of PT. Arifindo Adiputra Ariaguna. A quantitative approach was used, with data collected through questionnaires. The findings of this research are expected to contribute to the development of human resource management theory and serve as a reference for property companies in improving employee performance through enhanced motivation and job satisfaction. The completion of this proposal was made possible with the support and guidance of various academic and personal contributors who played an important role in the success of this research. This study is closely related to several key concepts, including leadership style, organizational culture, work motivation, job satisfaction, employee performance, mediating variables, human resource management, quantitative methods, and the property industry within PT. Arifindo Adiputra Ariaguna. This research is expected to contribute to the theoretical literature on human resource management by emphasizing the interrelationships and roles of each variable in shaping employee performance effectively and sustainably, as well as serving as an important reference for property companies in developing comprehensive HR management strategies